Green Taxonomy and its Implications for UAE - Yun, Chi Young (2022)
With the growth of green finance, policies and regulations are important tools to encourage and support capital flow. Previously backed mainly by public funds, the rise of Environment, Sustainability, and Governance (ESG) in private sector calls for clarity and guidance to make informed decisions. Green Taxonomy classifies economic activities allowing stakeholders to know whether their investments are environmentally sustainable. Accordingly, the purpose of this paper is to examine existing green taxonomies and find implications for UAE. As a result, this paper suggests UAE to develop a legally binding taxonomy, create a platform with private sector expertise, and to design a standardized guiding system. This paper makes contributions to better understanding green taxonomy and offers practical recommendations for UAE in its preparation for taxonomy implementation.